A case of refractory hypoxia and shock due to drug overdose successfully managed with ECMO first time ever in Bangladesh (Bangladesh Critical Care Journal, 2022)
A 36 -year-old female developed refractory cardiac and respiratory failure after self-declared ingestion of unknown amount of propranolol, benzodiazepine and few other unknown drugs in unknown dose. She also had vomiting followed by aspiration pneumonia. Despite giving adequate I/V fluid, antibiotics, activated charcoal, lipid emulsion, intravenous sodium bicarbonate and inotropic support, she became hypotensive and developed acute heart failure with pulmonary edema. This patient was managed with extracorporeal membrane oxygenation (ECMO) for 72 h, she survived without any deficit. This records country’s first ever use of extracorporeal membrane oxygenation in any patient. In this particular case when traditional antidotes were insufficient to prevent collapse, ECMO was introduced in the form of extracorporeal life support (ECLS) to maintain perfusion, reduce vasopressor requirements, and maintain oxygenation and carbon dioxide removal from blood. With increasing expertise and availability, extracorporeal membrane oxygenation should be considered in patients who develop cardiac or respiratory failure due to any cause, refractory to conventional therapy.Bangladesh Crit Care J September 2022; 10(2): 142-145